ZnO/carbon hybrids derived from polymer nanocomposite precursor materials for pseudocapacitor electrodes with high cycling stability. (14th February 2018) - Zhao, Yepin; Wang, Zongyu; Yuan, Rui; Lin, Yu; Yan, Jiajun; Zhang, Jianan; Lu, Zhao; Luo, Danli; Pietrasik, Joanna; Bockstaller, Michael R.; Matyjaszewski, Krzysztof
Abstract: A facile new route for fabricating carbon/zinc oxide (carbon/ZnO) hybrid materials suitable for pseudocapacitor electrodes with high cycling stability is presented. The synthesis of carbon/ZnO nanocomposites involved the uniform dispersion of octylamine (OA) capped ZnO nanocrystals into poly(styrene- r- acrylonitrile) (PSAN) copolymers and the subsequent pyrolysis of the nanocomposite precursor material to form the carbon/ZnO hybrid. PSAN copolymers with two different chain lengths were prepared to illustrate the effect of chain length on structure and properties of the composites. For all cases, the pyrolysis of ZnO-OA/PSAN precursor blends resulted in the formation of disperse ZnO/carbon core-shell hybrid structures. The accessible surface area was found to increase with molecular weight of matrix chains. The ZnO/carbon composites exhibited a specific capacitance of 145 F g −1 at the scan rate of 2 mV s −1 . In addition, 91% of the initial capacitance was obtained after 10, 000 charge/discharge cycles. The versatility of the synthetic process should render the presented method attractive for the fabrication of a wide range of carbon/transition metal oxide hybrid materials. Graphical abstract: Image 1 Highlights: A facile synthesis of carbon/ZnO hybrid materials is presented. Nanoporous carbon are synthesized from random copolymers. Capacitance and cycling stability of carbon/ZnO hybrids is demonstrated.